Central retinal artery occlusion in a young child affected by COVID-19: a first case report - Giulia Abbati; Camilla Fazi; Pina Fortunato; Sandra Trapani (BMC, 2023)
Abstract Background Central retinal artery occlusion (CRAO) is an ophthalmic emergency, and its etiology is generally ascribed to vessel occlusion by a thrombus or embolus, eventually due to a hypercoagulable state. CRAO occurrence is described even in the pediatric population, but its incidence is very rare. SARS-CoV-2 infection has a multitude of presentations, and almost any organ may be involved including the ocular district. Cases of CRAO in patients affected by COVID-19 are reported in the literature in the adult population, but not in the pediatric one. Case presentation We describe the case of a six-year-old otherwise healthy girl, who presented a sudden and complete bilateral vision loss after a one-day fever. All the clinical, ophthalmological, laboratory and instrumental investigations led to the diagnosis of a right CRAO and the suspicion of a contralateral posterior optic nerve affection. These manifestations could not be ascribed to any etiological condition apart from the documented ongoing mild SARS-CoV-2 infection. Treatment with anticoagulants and steroids was tried but the visual outcome was poor during the one-month hospitalization and at the last follow-up. Conclusions To the best of our knowledge, this is the first report of CRAO in the course of SARS-CoV-2 infection in the pediatric age. In our review of the literature, we found few cases of CRAO in adults with COVID-19; we highlighted differences in anamnestic, clinical, and interventional aspects and therefore we tried to summarize the state of the art on this topic to facilitate further studies. Even if rare, the prognosis of CRAO is poor and the thrombolytic treatment could be effective only if rapidly administered, so the disease suspicion should be high in a patient with sudden vision loss, also in pediatric age.